Acetylation and hydration treatment of recombinant spider silk fiber, and their characterization using 13C NMR spectroscopy. (14th March 2022) - Asakura, Tetsuo; Matsuda, Hironori; Aoki, Akihiro; Naito, Akira
Abstract: Spider dragline silks continue to attract many researchers because of the excellent mechanical properties and supercontraction behavior. In this paper, acetylation and hydration treatments of recombinant spider silk protein (RSP) were performed to improve the mechanical property of the RSP fiber. Both treatments increased the tensile strength significantly, while hydration treatment doubled the elongation-at-break of RSP fiber although acetylation did not change the elongation-at-break. Thus, remarkable increase in the toughness was attained by hydration treatment. A combination of three kinds of 13 C solid-state NMR techniques was used to elucidate changes in the structure and dynamics of both non-acetylated and acetylated RSP fibers by hydration. From the NMR studies, it is noted that staggered packing arrangement of polyalanine crystalline region changed to rectangular arrangement by acetylation. By hydration, the mobilities of the glycine-rich region increased remarkably, while those of the crystalline polyalanine region did not change. Graphical abstract: Image 1 Highlights: Acetylation and hydration treatments of recombinant spider silk protein (RSP) were performed. Both treatments increased the tensile strength of RSP fibers significantly. Hydration effect was studied for the RSP fibers with and without acetylation by13C solid-state NMR. By hydration, mobilities of Gly-rich region increased remarkably, while polyalanine region did not.